Novel bionic and clean de-icing bituminous composite material by autocrine microcapsule production with a temperature responsive character. (15th August 2021) - Su, Jun-Feng; Xie, Xin-Ming; Wang, Li-Qing; Gao, Xu
Abstract: Inspired by the bionic anti-icing structure of bird feather through autocrine oil, the aim of this work was to synthesize an intelligent and clean bituminous composite material for long-life anti-icing pavement based on a kind of autocrine microcapsule product with temperature responsive character. These microcapsules were prepared by an in-situ polymerization with a high methylether melamine formaldehyde (HMMM)/polyvinyl alcohol (PVA) blending shell material. Microstructure analysis results showed that the microcapsule shell had a polymer cross-linked HMMM structure as skeleton. All microcapsule samples had an initial decomposition temperature higher than 200 °C, which was suitable for bitumen pavement. PVA gel was filled in the skeleton network to block the holds against the leakage of core material. The temperature sensitivity of PVA could control the releasing rate of core material because of the open of porous structure in shell. At the same time, it was found that even under a low temperature under zero degree, the core material still had a capability of penetration through the shell of microcapsules. The anti-icing capability of bituminous composite had a sharply increase based on the ice shear force tests. Graphical abstract: Illustration of de-icing methods of bituminous pavement, (a) spraying de-icing agent on pavement directly, (b) electric-heating conversion method based on the pre-buried metallic conductor, (c) penguins in Antarctica with anti-icing wings, and (d) autocrine microcapsules containing de-icing agent base on temperature responsive character. Image 1 Highlights: Autocrine microcapsule was fabricated for bionic de-icing bitumen. Microcapsules had a temperature responsive character. Anti-icing capability of bitumen with microcapsules had a sharply increase.